2023
DOI: 10.1177/08862605231218684
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Links Between Friendship Quality and Peer Victimization Among Middle Adolescents

Juan Cao,
Wen Yuan,
Xiaodan Xu
et al.

Abstract: There is a robust association between friendship quality and victimization in adolescence; yet, it remains unclear whether friendship quality may be linked causally with different forms of victimization in middle adolescence. To fill this gap, this study examines the bidirectional associations of friendship quality and relational/verbal victimization with data collected at two time points, 6 months apart, in a sample of 671 middle Chinese adolescents ( Mage = 15.63, SDage = 0.73, 49% males). Cross-lagged panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…In a study, especially for male students, friendship qualities were found to be both a negative factor and a positive preventive factor. In the same study, it was suggested that friend relationships should also be questioned in bullying prevention programs (Cao et al, 2023).…”
mentioning
confidence: 98%
“…In a study, especially for male students, friendship qualities were found to be both a negative factor and a positive preventive factor. In the same study, it was suggested that friend relationships should also be questioned in bullying prevention programs (Cao et al, 2023).…”
mentioning
confidence: 98%